The Role of Pre-Pregnancy Body Mass Index (BMI) in Predicting Maternal Serum Leptin - Faghani Aghoozi 1, Marzieh; Tehranian 2*, Najmeh; Ramezani Tehrani 3, Fahimeh; Hamta 4, Amir; Amreian 5, Malihe; Kiani 5, Mahdieh; Joz Mohtashami 6, Mona; Mirzamoradi 7, Masoumeh (Shahroud Journal of Medical Sciences, 2019)
Background: The key role of leptin is regulation of appetite and body lipid and pregnancy is a condition associated with overeating, reduction in heating and adaptation of lipid cells, culminating in increased body fat mass. So, this study was conducted to examine the relationship between changes in pre-pregnancy BMI and leptin.Methods: This Longitudinal study was conducted on 45 women in the first trimester of pregnancy using a longitudinal approach and convenience sampling method in Tehran city in 2015. The mothers in terms of pre-pregnancy BMI were divided into two groups: group A (n=22 with normal BMI) and group B (n=23 with high BMI), with maternal serum leptin being taken in 6-12 weeks and 15-20 weeks of pregnancy and measured by enzyme-linked immunosorbent assay (ELISA). The statistical data were analyzed by SPSS V.21 using Kolmogorov Smirnov, independent t-test, two-sample Chi square, Mann-Whitney, Regression, Pearson and Landa tests with P.V<0.05.Results: The mean age of mothers in the present study was 27.47±5.55 years with a minimum age of 19 and a maximum age of 37 years. The mean plasma leptin of the first and second trimesters of pregnancy was significantly higher in the high BMI group than in the normal group. The correlation showed that the first trimester leptin and changes in leptin levels of pregnancy with pre-pregnancy BMI were significantly higher in the normal group (P=0.04 and P=0.003).Conclusions: BMI before and during pregnancy can be a predictor of maternal serum leptin in pregnancy weight gain.